How word-image relationships in children's picture books adapt across levels: A multimodal analysis - Al Farisi, Muhamad Fanni; Kushartanti, Bernadette; Purwanto, Dwi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
Children’s picture books apply a levelling system to adjust linguistic complexity according to the reader’s developmental stage. Despite having constitutive elements of text and images, their interdependent relationships within this system receive less attention. While the relationships of texts and images in picture books have been extensively studied, there is still a gap in understanding how these relationships adapt across different reading levels. Applying Halliday’s systematic functional linguistics (2004), Kress and Leeuwen’s multimodal approach (2021), and Nikolajeva and Scott’s approach to picture books (2006), this research qualitatively and quantitatively examined thirty-four text-image pairs from two children’s picture books at low and high reading levels. This study aimed to reveal whether such an adaptation exists and, if so, to what extent. The findings confirm that an increasing complexity in text-image relationships. The lower-level picture book exhibits three types of text-image relationships: enhancing, complementary, and counterpointing. The higher-level book, however, shows four types, incorporating a contradictory relationship alongside the other three. These findings suggest that the increasing complexity in children’s picture books occurs not only in linguistic aspects but also within multimodal relationships between texts and images, highlighting the need for picture book authors and educators to design or select picture books that progressively introduce multimodal complexity.